The outcome of pregnancy in a kidney transplant patient: a case report and review of the literature - Glišić, Andreja; Divac, Nevena; Gojnić Dugalić, Miroslava; Kastratović Kotlica, Biljana; Vavić, Neven; Cerovac, Nataša; Prostran, Milica (Vojnosanitetski pregled, 2017)
Introduction. The possibility of a term pregnancy with favorable maternal and neonatal outcome is one of the greatest advances in kidney transplantation, though concerns still exist regarding the safety of the mother, fetus, and graft. The use of immunosuppressive medications during pregnancy is related to possible fetal adverse effects. Case report. We report a course of a pregnancy in a patient with a kidney transplant. The patient was treated with immunosuppressive therapy (tacrolimus, azathioprine, and prednisolone) during the pregnancy. The outcome of the pregnancy was without maternal and neonatal complications. Serum creatinine levels were stable and no acute organ rejection occurred during pregnancy. Significant elevation of the D-dimer and coagulant factors II, VII, IX and X were noticed during the third trimester. This could be partially attributed to azathioprine, which was a part of the immunosuppressive regimen. On the other hand, there were no radiological or clinical signs of thromboembolism, but low-molecular-weight heparin prophylaxis was immediately initiated. Cesarean section was performed at the 39th gestational week and a healthy female infant was delivered with a birth weight of 3,150 g and Apgar score 9. Conclusion. Pregnancies of kidney transplant recipients are high-risk and require a multidisciplinary approach. Careful clinical follow-up is a prerequisite for favorable outcome.